Bibliometric Analysis of Arabic Proficiency based on Scopus-Indexed Articles - Yunita Yunita; R. Umi Baroroh Baroroh; Sri Utami; Yulianingsih Riswan; Ike Fitriana Saraswati (Arabic Education Department, Islamic Studies Faculty, Universitas Muhammadiyah Malang, 2024)
This study examined the evolution of research on Arabic language competency, including which nations have made substantial contributions, what topics come up regularly, and what research subjects are available to those interested in the discipline. This research is a bibliometric analysis on academic papers dealing with Arabic speaking skills. The total of 155 articles are collected from the Scopus website, then uploaded to the biblioshiny application using R-studio Cloud. All information is extracted to CSV format for data analysis and then entered the VOS viewer. The results show that (1) due to historical reasons and proximity to the Arabic language, Israel is the country with the largest number of authors on